Esophageal cancer mortality trends in the United States: a comprehensive longitudinal study (1999–2023) using CDC WONDER data - Yang, Xuefei; Shao, Yinyan; Guo, Junhua; Huang, Ting; Zhou, Heran (Frontiers in Public Health, 2025)
BackgroundEsophageal cancer continues to pose a significant public health challenge worldwide. However, the extent to which advancements in treatment have reduced mortality at the population level remains unclear. This study examines trends in esophageal cancer mortality in the United States from 1999 to 2023, focusing on variations based on sex, ethnicity, urbanization level, census region, and age group.MethodsMortality data were obtained from the Centers for Disease Control and Prevention’s Wide-Ranging Online Data for Epidemiologic Research (CDC WONDER) database using ICD-10 codes (C15.0–C15.9) to identify esophageal cancer-related deaths. The analysis included individuals aged 25 years and older. Temporal trends in age-adjusted mortality rates (AAMR) were analyzed using the Joinpoint Regression Program. Data were stratified by census region, metropolitan/non-metropolitan residence, and state. Annual percentage change (APC) and average annual percentage change (AAPC) were calculated along with their 95% confidence intervals (CI).ResultsBetween 1999 and 2023, a total of 357,606 deaths from esophageal cancer were recorded. A significant decline in the mortality rate was observed over this period, with the overall AAMR decreasing from 6.74 to 5.61 per 100,000, corresponding to an AAPC of −0.81* (*p-value < 0.05). Decline in the mortality rate was evident across nearly all ethnic groups, with the exception of the non-Hispanic (NH) white group. The most significant reduction was observed among non-Hispanic Black individuals (AAPC: −4.07*). Significant sex-based disparities persisted throughout the study period, with men consistently experiencing higher mortality rates than women. Geographically, mortality trends diverged: metropolitan areas experienced a significant decline (AAPC: −1.09*), whereas non-metropolitan areas experienced a significant increase (AAPC: 0.48*). Pronounced regional disparities were also noted, with the western and northeastern regions demonstrating the most substantial improvements. Age-specific analyses revealed a significant reduction in the mortality rate across the majority of age groups; however, among adults aged 85 years and older, the mortality rates remained stable.ConclusionDespite an overall decline in the mortality rate of esophageal cancer, significant disparities persist across geographic, urban–rural, and age subgroups. These findings highlight the need for targeted public health interventions to address ongoing inequalities, particularly among NH white individuals, those living in non-metropolitan areas, and older adult.